Memahami Ulang Makna Sosio-Ekologis Abad 21: Kespesiesan Manusia dan Personitas Alam dalam Anthropocene Melalui Actor-Network Theory - Fiktor Jekson Banoet (KENOSIS: Jurnal Kajian Teologi, 2022)
Tendency of the post-positivism sociology family to define the social meaning of humans as a way of living together between humans. The social meaning is drawn from the interactions between them and has not included the associative rules with the ecosphere (biotic and abiotic) as forming the social meaning. And conversely, certain parties, from among scientists, even environmental activists, do not include the definition of the environment as having a "personality". In the midst of the ecological crisis context, this paper tries to re-interpret this meaning socio-ecologically. The goal is to obtain alternatives to respond to the environmental crisis in Indonesia. We conceptualize the perspective of Actor Network Theory, or what is also called Actant Rhizome, by Bruno Latour. He discusses that social meaning is no longer centered on humans and society is no longer human society. Rather, society is any non-human entity in the ecosphere, technosphere and sociophere (human environment) which satisfies the presupposition of interaction, which he calls “active”. For Latour, in an era of ecological crisis, many people will mutate themselves according to that crisis. Theologically, it can then be further reflected in the socio-ecological meaning of society, including the mutated whole.AbstrakKecenderungan rumpun sosiologi pascapositivisme mendefinisikan makna sosial manusia sebagai cara hidup bersama antarmanusia. Makna sosialnya ditarik dari interaksi antara manusia dan belum memasukkan kaidah asosiatif ke dalam ekosfer sebagai pembentuk makna sosial tersebut. Sebaliknya, pihak tertentu, dari kalangan saintis, bahkan pegiat lingkungan kurang memasukan definisi lingkungan hidup sebagai yang memiliki ‘kepribadian’. Di tengah konteks krisis ekologi di Indonesia, tulisan ini mencoba memaknai ulang makna tersebut secara sosio-ekologis. Tujuannya supaya memperoleh alternatif menanggapi krisis lingkungan. Studi ini mempertimbangkan perspektif Teori Jaringan-Aktor (actor-network theory), atau yang juga disebut Actant Rhizome, oleh Bruno Latour. Ia mendiskursuskan bahwa makna sosial tidak lagi berpusat pada manusia dan masyarakat bukan saja masyarakat manusia. Tetapi juga setiap entitas non-manusia dalam ekosfer, teknosfer dan sosiofer yang memenuhi pengandaian interaksi, yang ia sebut ‘aktan’.